(Re)Entering the Workforce: An Historical Perspective on Family Responsibilities Discrimination and the Shortcomings of Law to Remedy It - Elizabeth Roush (Washington University Journal of Law & Policy, 2009)
This Note argues that the story about ―women‘s recent entry into the workplace is a flawed one, and that this misunderstanding of the historical interaction between work and caregiving has led to flawed analyses and propsed solutions from many scholars and popular authors. Recognizing that only recently have women‘s and caregivers‘ carework become "invisible" as part of the economy sheds light on the best solutions to Family Respinsibility Discrimination.
Keywords: Work & amp; family; Employment discrimination; Work-life balance; Working mothers; Gender; Equal Employment Opportunity Commission; EEOC